Prevalent vertebral deformities predict hip fractures and new vertebral deformities but not wrist fractures. Study of Osteoporotic Fractures Research Group. - Black, D; Arden, N; Palermo, L; Pearson, J; Cummings, SR (Blackwell Publishing Inc., 1999)
Although vertebral deformities are known to predict future vertebral deformities, little is known about their ability to predict other osteoporotic fractures. We examined the association between prevalent vertebral deformities and incident osteoporotic fractures in the Study of Osteoporotic Fractures, a prospective study of 9704 women aged 65 years and older. Prevalent vertebral deformities were determined morphometrically from spinal radiographs at baseline and incident deformities from repeat spinal radiographs after a mean of 3.7 years. Appendicular fractures were collected by postcard every 4 months for a mean of 8.3 years. During follow-up, 389 women with new vertebral deformities, 464 with hip fractures, and 574 with wrist fractures were identified. Prevalent vertebral deformities were associated with a 5-fold increased risk (relative risk 5.4, 95% confidence interval [CI] 4.4, 6.6) of sustaining a further vertebral deformity; the risk increased dramatically with both the number and severity of the prevalent deformities. Similarly, the risks of hip and any nonvertebral fractures were increased with baseline prevalent deformity, with relative risks of 2.8 (95% CI 2.3, 3.4) and 1.9 (95% CI 1.7, 2.1), respectively. Risk increased with number and severity of deformities. These associations remained significant after adjustment for age and calcaneal bone mineral density (BMD). Although there was a small increased risk of wrist fracture, this was not significant after adjusting for age and BMD. In conclusion, the presence of prevalent morphometrically defined vertebral deformities predicts future vertebral and nonvertebral fractures, including hip but not wrist fractures. Spinal radiographs identifying prevalent vertebral deformities may be a useful additional measurement to classify further a woman's risk of future fracture.